The due process and the principal guidelines for a procedural model in the constitutional Rule of Law - Ticona Postigo, Víctor (2007)
The Government of laws comes from the Legislative State, whose essential element, among others, is the effective jurisdictional custodyof all the rights and liberties; in this perspective the author inspects the evolution of the denomination of Government of laws; he explains the jurisdictional custody and the due process like fundamental rights; if both rights have identity relation or are different; it also exposes his proposal on the matter; and finally it deals with the recognition of these two rights in the Peruvian Law.